Liquefaction resistance of bio-cemented calcareous sand - Xiao, Peng; Liu, Hanlong; Xiao, Yang; Stuedlein, Armin W.; Evans, T. Matthew (Soil dynamics and earthquake engineering (1984), 2018)
Coral reefs and other calcareous deposits may experience various types of significant dynamic loading, such as those from waves and earthquakes. When submerged and subjected to earthquake loading, the potential for liquefaction of calcareous deposits may cause a loss of human life and property; however, few studies have evaluated the liquefaction potential of calcareous sands relative to those conducted on silica sands. Accordingly, it is critical to study the cyclic resistance of calcareous sands as well as methods to mitigate their liquefaction potential. Microbial induced calcite precipitation (MICP) offers one such strategy that can be considered for improving the cyclic resistance of calcareous sands, particularly for those applications below existing infrastructure that would pose technical difficulties for traditional modes of ground improvement. This paper examines the effectiveness of MICP on the cyclic resistance of as a function of cementation solution (CS) content, effective confining pressure, and cyclic stress ratio (CSR) through a cyclic triaxial test program. The generation and accumulation of excess pore pressure and corresponding axial strains are compared across a range of treated and untreated sands. This study shows that the liquefaction resistance of clean calcareous sand may be significantly improved by the MICP treatment. Scanning electron microscope images are presented to help link the improvement in cyclic response to the microstructural features of the microbial-induced calcite and bio-cemented sand. •A series of cyclic tests on MICP-treated calcareous sand are presented.•Effect of cyclic shear ratio and confining pressure on shear resistance is investigated.•SEM images reveal the microstructural features of MICP-treated calcareous sand.